Occurrence of Geranium mascatense (Geraniaceae) in India and the speculations about its global distribution - Hurrah, Imtiyaz A.; Shukla, Aparna R.; Wagh, Vijay V. (Phytotaxa, 2023)
The delimitation and taxonomic status of Geranium mascatense Boiss. in India has not merely been in a state of flux, but also experience distributional inconsistency both at national and global level. The study aims at highlighting an extension to the global distribution range of this species and at resolving the chaos that exists about its taxonomy and distribution in India. The results are validated through detailed description, illustrations, digital photographs, macro and micro-morphological characters, comparison with allied species, taxonomic key, notes on taxonomy and distribution map of G. mascatense and its nearest kin, G. ocellatum.